Behavior to Adopt Sharia Insurance in The Midst of Pandemic with Religiosity as a Moderator Variable (Survey on Sharia Unit of Prudential Life Insurance) - A. Jajang W. Mahri; Juliana Juliana; Rifa Mutiara; Suci Aprilliani Utami; Dadang Munandar (Universitas Negeri Makassar, 2023)
This study aims to analyze the effect of attitudes, subjective norms, and perceptions of behavioral control on intentions and the effect of intentions on behavior with sharia life insurance. In addition, it raises religiosity variables that are used to moderate attitudes, subjective norms, and perceptions of behavioral control over intentions. The method in this research is causality method with quantitative approach. The sampling technique used was purposive sampling with a total sample of 130 PruSyariah participants throughout Indonesia. While the data analysis used the PLS-SEM approach. Findings: The results shows that attitudes and perceptions of behavioral control had a positive and significant effect on intentions, while subjective norms had no and no significant effect on intentions. The intention has a positive and significant effect on behavior. The moderating variable religiosity did not moderate attitudes, subjective norms, and perceptions of behavioral control in increasing intention, but religiosity is able to moderate between intention to behavior to adopt sharia life insurance. In an effort to increase public participation in sharia life insurance, the intention formed begins with a good evaluation of sharia life insurance itself and is strengthened by maturity and readiness both materially and other supporting things that make people confident and able to access sharia life insurance with easy. Sharia compliance is also a plus point to be able to increase intentions which then affect the behavior of sharia life insurance. This study studies the behavioral determinants of sharia life insurance which are influenced by intention. Where the determinants of intention studied are factors in the theory of planned behavior by bringing up religiosity as a moderating factor.